Influence of quertine on the free radical lipid peroxidation in patients with uronephrolithiasis comorbid with metabolic syndrom - Bilai, S. I.; Dovbysh, M. A.; Білай, Сергій Іванович; Довбиш, Михайло Афанасійович (Wydawca «Interdruk» Poland, Warszawa, 2021)
The pathogenesis of urolithiasis is partially determined by oxidative stress, whose main cause is an imbalance in the oxidant-antioxidant system, which is manifested by excessive formation of reactive oxygen species and weakening of the effectiveness of antioxidant protection. The research aims to study the effect of quertine on the processes of lipid peroxidation (LPO) in patients with UN comorbid with MS. Patients with UN of Group 1 (control) (n = 38) received traditional therapy. Group 2 (comparison) patients with UN comorbid with MS (n = 42) received, in addition to traditional therapy, conventional drugs that correct metabolic disorders. Group 3 (main) patients with UN comorbid with MS (n = 38) received quertine on the background of traditional therapy and drugs that correct metabolic disorders. During treatment, patients with UN demonstrated an accumulation of TBA-AP for the entire period of treatment with traditional therapy. The level of LPO intermediate products, namely of DC and TC, increased significantly after 14 days and after 1.5-2 months of follow-up, respectively. The content of endogenous α-tocopherol (α-TF) and glutathione reductase (GR) activity also decreased moderately after 14 days and after 1.5-2 months of treatment, respectively. In patients with UN comorbid with MS, inhibition of the intensity of LPO processes was observed, which was manifested in a moderate decrease in the pool of TBA-AP final product after 3-6 months to 0.82 ± 0.02 μmol / ml (p˂0.05). Thus, the use of quertine in combination with traditional therapy, drugs that affect metabolic processes, and differentiated uricostatic and uricolytic drugs contributed to the LPO processes normalization and the AOS restoration.
Keywords: quertine; lipid peroxidation; urate nephrolithiasis; metabolic syndrome